Shadow spell [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Cousins O'Dwyer trilogy, 2014)
"With the legends and lore of Ireland running through his blood, falconer Connor O'Dwyer is proud to call County Mayo home. It's where his sister, Branna, lives and works, where his cousin, Iona, has found true love, and where his childhood friends form a circle that can't be broken... A circle that is about to be stretched out of shape--by a long-awaited kiss. Meara Quinn is Branna's best friend, a sister in all but blood. Her and Connor's paths cross almost daily, as Connor takes tourists on hawk walks and Meara guides them on horseback across the lush countryside. She has the eyes of a gypsy and the body of a goddess...things Connor has always taken for granted--until his brush with death propels them into a quick, hot tangle. Plenty of women have found their way to Connor's bed, but none to his heart until now. Frustratingly, Meara is okay with just the heat, afraid to lose herself--and their friendship--to something more. But soon, Connor will see the full force and fury of what runs in his blood. And he will need his family and friends around him, when his past rolls in like the fog, threatening an end to all he loves.."--